Exploration of Financial Literacy Learning and Its Implementation in the Independent Curriculum at The High School Level - Rusli Situmorang; Elisabet Margareta `` Batubara; Sanggam Pardede (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
The issue in this research is that financial literacy learning has not yet been widely integrated into the Independent Learning Curriculum at the elementary school level. The purpose of this research is to identify financial literacy material in the Independent Learning Curriculum at the elementary school level. This study uses library research. Library research is a research method that is conducted by collecting library data, analyzing literature sources, reading selected literature sources appropriately, evaluating the most relevant sources to the research topic, and writing or recording a research report that includes a literature review. Based on the research results, it can be seen that the percentage of financial literacy material implementation at the school level largely applies investment material, with a percentage reaching 80%. The material for saving and financial management is 52%, recognizing risks and returns is 42%, budgeting material is 14%, understanding entrepreneurship is 12%, financial technology is 10%, understanding money is 6%, and the lowest is loans at 4%. Therefore, with this analysis, financial literacy is very necessary to be implemented at the high school level.